The influence of various coatings of hydroxyapatite bone carrier on the success of bone regeneration in rabbit calvarial defects: histomorphometric and histological analysis - Milutinović-Smiljanić, Sanja; Antonijević, Djordje; Mićić, Milutin; Biočanin, Vladimir; Sjerobabin, Nikola; Petrović , Božana; Danilović, Vesna; Jokanović, Vukoman (Vojnosanitetski pregled, 2022)
Background/Aim. The materials used nowadays for bone replacement do not fully meet the requirements for complete regeneration, which is why new ones are being tested. Despite numerous attempts to improve bone tissue regeneration, no fulfilling material has been found yet. This study investigated the influence of poly-lactide-co-glycolide (PLGA) and polyethyleneimine (PEI) as coatings for hydroxyapatite (HAP) bone carriers on bone tissue regenerative potential in rabbits’ calvarial defect. Methods. Calvarial defects measuring 6 mm in diameter were made in 19 skeletally mature rabbits. Defects were filled with one of the following materials: PLGA coated HAP (HAP + PLGA), PEI coated HAP (HAP + PEI), and bovine HAP – Bio-Oss® (positive control). Unfilled defects represented negative control. Histological analysis was performed in order to determine the inflammatory response of the host tissue. The formation of the new bone was evaluated using histomorphometric analysis. All analyses have been conducted in samples obtained 3, 6, and 9 weeks after implantation. Results. Three weeks post-implantation, a trend toward increased healing in the HAP + PLGA group compared to other investigated materials was noticed, with no statistically significant difference between the study groups (p > 0.05). However, after 6 and 9 weeks, significant healing was observed in favor of the HAP coated with PLGA compared to other groups (p < 0.05). Within this group, greater bone healing was observed compared to the HAP + PEI and Bio-Oss® groups. Conclusion. PLGA demonstrated greater coating potential compared to PEI with respect to osteogenesis improvement in bone reconstructive surgery.
Keywords: bone regeneration; histological techniques; materials testing; polymers; rabbits.